GOING CONCERN AUDIT DETERMINATION IN INDONESIAN AGRICULTURAL SECTOR - Mohamad Zulman Hakim (Universitas Pamulang, 2018)
The purpose of this research is to know the influence of debt to equity ratio(DER), company size (SIZE), current ratio (CR) and reputation of PublicAccounting Firm (KAP) to going concern audit opinion (GCAO) in agriculturalsector companies listed in Indonesia Stock Exchange period 2012-2016. The study population includes all agricultural sector companies listed in Indonesia Stock Exchange period 2012-2016. The sampling technique used purposive sampling technique with sample of 16 companies and 80 observations. Data analysis method used is panel data logistic regression analysis with using program EViews (Econometric Views) version 9.0. The results showed that the debt to equity ratio (DER) has a positive effect to going concern audit opinion (GCAO), the size of the company (SIZE) has a negative effect to going concern audit opinion (GCAO), current ratio (CR) and reputation of Public Accounting Firm (KAP) doesn’ t affect the going concern audit opinion (GCAO).